Sumoylation at chromatin governs coordinated repression of a transcriptional program essential for cell growth and proliferation - Neyret-Kahn, Hélène; Benhamed, Moussa; Ye, Tao; Le Gras, Stéphanie; Cossec, Jack-Christophe; Lapaquette, Pierre; Bischof, Oliver; Ouspenskaia, Maia; Dasso, Mary; Seeler, Jacob; Davidson, Irwin; Dejean, Anne (Genome Research, 2013)
Despite numerous studies on specific sumoylated transcriptional regulators, the global role of SUMO on chromatin in relation to transcription regulation remains largely unknown. Here, we determined the genome-wide localization of SUMO1 and SUMO2/3, as well as of UBC9 (encoded by UBE2I) and PIASY (encoded by PIAS4), two markers for active sumoylation, along with Pol II and histone marks in proliferating versus senescent human fibroblasts together with gene expression profiling. We found that, whereas SUMO alone is widely distributed over the genome with strong association at active promoters, active sumoylation occurs most prominently at promoters of histone and protein biogenesis genes, as well as Pol I rRNAs and Pol III tRNAs. Remarkably, these four classes of genes are up-regulated by inhibition of sumoylation, indicating that SUMO normally acts to restrain their expression. In line with this finding, sumoylation-deficient cells show an increase in both cell size and global protein levels. Strikingly, we found that in senescent cells, the SUMO machinery is selectively retained at histone and tRNA gene clusters, whereas it is massively released from all other unique chromatin regions. These data, which reveal the highly dynamic nature of the SUMO landscape, suggest that maintenance of a repressive environment at histone and tRNA loci is a hallmark of the senescent state. The approach taken in our study thus permitted the identification of a common biological output and uncovered hitherto unknown functions for active sumoylation at chromatin as a key mechanism that, in dynamically marking chromatin by a simple modifier, orchestrates concerted transcriptional regulation of a network of genes essential for cell growth and proliferation.